Minat Mahasiswa Akuntansi dalam Mengikuti Pendidikan Profesi Akuntansi (Ppa) ditinjau dari Gender dan Status Akreditasi Program Studi - Sudaryono, Eko Arief; P, Angger Tunggul; Setiawan, Doddy (Universitas Muhammadiyah Yogyakarta, Indonesia, 2005)
This research aims to examine accounting students interest in joining professional accounting education based on gender and accreditation of the study program. Respondents of this research are final year accounting students in Solo, Yogyakarta and Semarang. We use anova test in this research. The results shows that: (1) there are no significant differences in accounting students’ interest in joining professional accounting education based on gender (2) there are significant differences in accounting students’ interest in joining professional accounting education based on the accreditation status of the study program (3) there are significant differences in accounting students’ interest in joining professional accounting education based on gender and the accreditation status of the study program simultaneously.